PENATALAKSANAAN DIET JANTUNG DAN STATUS GIZI PASIEN PENDERITA HIPERTENSI KOMPLIKASI PENYAKIT JANTUNG RAWAT INAP DI RUMAH SAKIT UMUM BANDUNG MEDAN - Diza Fathamira Hamzah (Prodi Kesehatan Masyarakat FKM UIN Sumatera Utara Medan, 2017)
ABSTRACT   One of non medical treatment of heart hypertension complication sufferers is by having the heart diet well for reach a normal nutritional status. The main nutrient compositions of this diet are calory, protein, fat, carbohydrate and sodium. This research aims to know the represent of the management of heart diet and nutritional status of hospitalized heart hypertension complication patients in Bandung General Hospital of Medan in 2012. The research was a descriptive study with number of sample 35 hospitalized heart hypertension complication patients in Bandung General Hospital of Medan, which was taken by using consecutive sampling. The results showed that the type of indication heart has been accordance with the standard heart diet type IV. Most of the patients have an obedience action in medium category (94.3%) in having the heart diet which was provided from the hospital. Beside, most of the nutritional status are normal (82.9%). It is recommended to the Bandung General Hospital of Medan especially the installation of nutrition to have a dietary guidelines. Beside it is good to make a hospital policy for hospitalized patients to have the diet well. Keywords: hypertension, heart complication, heart diet, nutritional status